Analisis Perbandingan Kualitas Buku Teks Bahasa Arab Kelas VI Terbitan Kemenag dan Erlangga - Ikrima, Ikrima; Sunarko, Asep; Alawiyah, Luluk (Edu Journal Innovation in Learning and Education, 2024)
This research is motivated by the large number of textbooks circulating among Madrash Ibtidaiyah which are used by teachers and students in the learning process. This research aims to describe the comparison of the quality of class VI Arabic textbooks published by the Ministry of Religion and Erlangga based on the theory of W.F. Mackey. This research uses qualitative research methodology in library research. This research focuses on the quality of books in terms of selection, gradation, presentation and repetition. The results of comparative analysis research on Arabic language textbooks for class VI published by the Ministry of Religion and Erlangga were reviewed based on W.F. Mackey's theory, namely selection, gradation, presentation and repetition. This Class VI Arabic textbook released by the Ministry of Religion has high standards both in terms of selection and assessment. Meanwhile the quality is very good in terms of repetition and presentation. From the four aspects of presentation, the Arabic language textbook for class VI produced by Erlangga is of very high quality. The textbooks published by Erlangga are better than those published by the Ministry of Religion, based on the findings of the quality inspection of the two volumes.